MODERN PRINCIPLES OF THE DEVELOPMENT OF ENOGASTRONOMIC TOURISM IN THE ODESSA REGION - KALYNA, Tеtiana; RUDNICHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Of particular importance for the territories is the development of industries that form a multiplier effect, positively influence adjacent branches of the national economy, contribute to the creation of new jobs, increase the mobility of the population, contribute to the budgets of all levels, ensuring the economic growth of the territory. Gastronomy is a significant resource and source in the formation of the uniqueness of different territories: tourists who visit destinations get to know local attractions, show interest in national cuisine, local traditions, cultural and ethnic features of food and drink preparation. The Odesa region has significant potential for the development of food and wine tourism and is one of the most promising innovative areas in the Odesa tourist market.The purpose of the publication is to study the peculiarities of the functioning of eno-gastronomic tourism in the Odesa region and its impact on the economic and social development of the region and rural areas.The article examines the essence and nature of the popularity of domestic tourism. It is noted that the development of domestic tourism in the region can be considered as a factor in the growth of the local economy, the production of a tourist product on the basis of available tourist and recreational resources, the consumption of which will contribute to the development of the regional economy. It is noted that gastronomic and wine tourism is a tool that will allow promoting little-known destinations, help revive the local economy and preserve traditions. The essence and significance of gastronomic tourism is determined and it is substantiated that eno-gastronomic tourism is gaining significant popularity, especially in regions with available resources for its development. Odesa region is one of the most favorable for the development of food and wine tourism. Specific features that will lead to the development of food and wine tourism in the region have been determined. The actual principles of the "Wine and Taste Road of Ukrainian Bessarabia", which involves the display and popularization of enogastronomic tourist routes and their importance for the development of the region and rural areas, have been defined.The development of food and wine tourism does not require significant investments, special or unique infrastructural developments. The effectiveness of the development of eno-gastronomic tourism is directly related to the ability of tourist operators to competently organize gastronomic tours, use the opportunities of integration at the regional level, adapt successful foreign experience and implement it in the domestic sphere of the tourism industry
Keywords: domestic tourism; gastronomic tourism; enogastronomic tourism; region; socio-economic development